KEBIJAKAN RUMAH LAYAK HUNI PEMERINTAH KOTA PEKANBARU DALAM MENGATASI KEMISKINAN TAHUN 2016 - Irfan, Muhammad; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In order to achieve the vision and mission of Pekanbaru City and poverty alleviation of Pekanbaru city government since 2012 has determined the program of Rumah Diak Huni. That is a program that helps the provision of housing needs for poor families and in realizing the national program of a million homes. In addition, as an effort to accelerate and equitable development for the welfare of the community. The research problem can be formulated as follows: "How is the Housing Policy Eligible Pekanbaru City Residents in Overcoming Poverty in 2016?" The purpose of this study are: "To Know House Decent Policy Huni Pekanbaru Municipal Government in Overcoming Poverty in 2016 ". Qualitative research methods. This research was conducted in Pekanbaru City. Primary data sources through interviews as well as secondary data sources. Data analysis technique is conducted by qualitative descriptive analysis The variables of Van Meter and Van Horn are described in the following research results: Basic measures and policy objectives, helping Pekanbaru City residents have a habitable home that accelerates the community to achieve welfare. Policy sources, Pekanbaru Municipality government is not Have sufficient funds available to meet the entire society that meet the criteria for a decent home, human resources available in the home program have good qualifications ranging from the level of education, experience, and kepangkatan.Komunikasi between organizations and implementation activities, There is no problem of inter-organizational communication. Characteristics of implementing agencies, the characteristics are adjusted to the applicable regulations. The economic, social and political conditions of the political conditions of the legislative election and presidential election in 2014 have little or no effect on the home program Habitation implemented by the government of Pekanbaru City, the economic problem is the limited Budget Acceptance and Expenditure (APBD) owned by the government of Pekanbaru City. The tendency of implementors, executors to run as desired, this is known from the lack of protest about the implementation of the house habitable program, the mechanisms ranging from proposal to developmentcarried out in accordance with the rules, and no problems experienced by the contractor implementing the development.Keywords: Policy, habitable home